1999
DOI: 10.1103/physrevb.60.1480
|View full text |Cite
|
Sign up to set email alerts
|

Transverse effective charge and its pressure dependence in GaN single crystals

Abstract: The pressure dependence of the A 1 (TO) and A 1 (LO) phonon modes of bulk, single crystals of wurtzite GaN has been measured by Raman scattering in a diamond-anvil cell up to 40 GPa. The measured phonon frequencies have been used to determine the LO and TO phonon-mode Grüneisen parameters and also the value of effective transverse charge e T *ϭ2.6 and its pressure derivative de T */dPϭϪ2.4ϫ10 Ϫ3 GPa Ϫ1 . The experimentally obtained values are compared with results of calculations by means of tight-binding form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 19 publications
3
19
2
Order By: Relevance
“…The Raman spectrum for sample no. 7 shows a broad peak between the E 2 (high) and A 1 (LO) phonons, which may be related to lattice disorder as a similar observation has been made on a high-temperature-annealed GaN film [20].…”
Section: Article In Pressmentioning
confidence: 65%
See 1 more Smart Citation
“…The Raman spectrum for sample no. 7 shows a broad peak between the E 2 (high) and A 1 (LO) phonons, which may be related to lattice disorder as a similar observation has been made on a high-temperature-annealed GaN film [20].…”
Section: Article In Pressmentioning
confidence: 65%
“…Using Raman factor of 3.2 (GPa cm) À1 for A 1 (LO) mode according to Perlin et al [20], the A 1 (LO) Raman shifts caused by strain may be deducted from the total A 1 (LO) frequency shift. The Raman shifts due to phonon-plasmon coupling are listed in Table 2.…”
Section: Article In Pressmentioning
confidence: 99%
“…In order to investigate the effect of built-in strains on the high-pressure Raman spectra of w-InN epilayers, we have investigated five different InN samples (see Table I). These measurements were partly motivated by the fact that, in spite of the small number of works dealing with the highpressure vibrational properties of w-InN 4-7 and of w-GaN, [31][32][33][34] the dispersion of reported pressure-coefficient values in these two compounds is relatively high. For instance, in the case of the E 2h mode of w-InN, pressure coefficients ranging from 4.74 cm Figure 7 shows the linear pressure coefficients measured for the zone-center E 2h modes in all the samples investigated in this work.…”
Section: 2829mentioning
confidence: 99%
“…Perlin et al found that the separation decreased with increasing pressure [78] but had combined data taken on different samples. Our results, shown in Fig.…”
Section: C)mentioning
confidence: 99%